The networking concept as an ethical interpretative key of the sustainable development principle - Marczak, Łukasz (Studia Ecologiae et Bioethicae, 2019)
The aim of the study is to present the concept of networking (Retinität), developed on the basis of Christian social ethics, which has become a key to the interpretation of the sustainable development principle. The article presents a network based on the Munich social ethics of Markus Vogt, who recognises this concept in Christian social ethics as a fundamental strategy of action to protect the natural environment, also affecting the dynamics of economic processes. Retinität has become one of the determinants of choosing the sustainable development principle on the basis of Christian social ethics as a result of the analysis of ethical and social principles systems.